2015
DOI: 10.1103/physrevc.92.015504
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino-pair bremsstrahlung from nucleon-nucleon scattering

Abstract: PACS number(s): 12.15. Ji, 13.75.Cs, 24.80.+y, 2 Abstract Background: Neutrino-pair bremsstrahlung processes from nucleon-nucleon scattering NNνν ( nnνν , ppνν , and npνν ) have recently attracted attention in studies of neutrino emission in neutron stars, because of the implications for the neutron star cooling. The calculated NNνν emissivities within the neutron star environment are relatively insensitive to the two-nucleon dynamical model used in the calculations, but differ significantly from those obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The general structure of the diagrams is depicted in Fig. 15, but without the gauge bosons connecting the lines in many permutations (see, e.g., [76,77] and references therein). However, in all diagrams there is a single unbroken neutrino line, so the self-energy is linear in f .…”
Section: E Nucleon-nucleon Bremsstrahlungmentioning
confidence: 99%
“…The general structure of the diagrams is depicted in Fig. 15, but without the gauge bosons connecting the lines in many permutations (see, e.g., [76,77] and references therein). However, in all diagrams there is a single unbroken neutrino line, so the self-energy is linear in f .…”
Section: E Nucleon-nucleon Bremsstrahlungmentioning
confidence: 99%
“…Similar expressions can be written down for np and pp bremsstrahlung, resulting in pp ν < np ν < nn ν (see for instance [31]). The calculations show that the use of the realistic T N N matrix instead of the OPE leads to the suppression of the neutrino emissivity approximately by a factor of four [so α ex nn (T N N ) ≈ 0.2] [258,270,[278][279][280]. Note that the inclusion of additional meson exchange terms [271,278] results in a better agreement with T -matrix calculations.…”
Section: Neutrino Emission Of Nuclear Mattermentioning
confidence: 81%
“…Note that the inclusion of additional meson exchange terms [271,278] results in a better agreement with T -matrix calculations. Li et al [280] quantified the limits of applicability for the soft bremsstrahlung theorem for a certain realistic model of the nucleon interactions. They found that the approximation ( 110) is accurate within 10% up to ω ν = 60 MeV.…”
Section: Neutrino Emission Of Nuclear Mattermentioning
confidence: 99%
“…The latter modifications are quite uncertain. For instance, using the free or in-medium scattering matrix in place of the one-pion exchange matrix element leads to the reduction of the 𝑛𝑛 bremsstrahlung rate by a factor of 2-4 (e.g., Van Dalen, Dieperink & Tjon 2003;Li et al 2015). On the other hand, in the so-called 'medium-modified one-pion exchange model' (e.g., Voskresensky 2001), the bremsshtrahlung rate is predicted to be increased by a factor of 100 at densities larger than the nuclear saturation density.…”
Section: Discussionmentioning
confidence: 99%